Extraction, purification, and identification of total saponins from hazel mushroom and its application evaluation - Fang, Yuan; Kan, Wenjun; Yimamu, Yilizhati; Cui, Xinyu; Luo, Yanan; Cao, Xueling (Frontiers in Nutrition, 2026)
A novel approach was formulated for extracting saponins from hazel mushroom (SHM) via microwave-assisted extraction (MAE). Response surface methodology was employed to refine and optimize how extraction parameters affect extraction efficiency. This study examined parameters such as solid–liquid ratio (1:15–1:30 g/mL), extraction power (from 200 to 600 W), extraction duration (between 5 and 25 min), and ethanol concentration (from 40 to 80%). The identified optimal extraction parameters were as follows: ethanol concentration of 57.52%, solid-to-liquid ratio of 1:25 g/mL, extraction time of 20.00 min, and extraction power of 369.75 W. When these ideal conditions were applied, the extraction yield of SHM reached a notable 34.61%. Using UPLC/Q-TOF-MS, 22 compounds were identified from the SHM obtained from MAE, primarily consisting of sesquiterpenes, adenosine, sterols, purines, and diterpenes. Finally, the anticancer effects of SHM were analyzed. The results indicated that SHM exhibited anti-tumor activity and antioxidant activity. For the first time, this research conducted an in-depth analysis of the total saponin extract derived from hazel mushroom. The findings of this study may offer a valuable methodology for optimizing the extraction process, ensuring quality control, and evaluating bioactivities. This is the first systematic study on saponins from hazel mushroom.